Edney, Matthew H. (2019). Cartography: The Ideal and Its History - Nadal, Francesc (Documents d'Anàlisi Geogràfica, 2023)
Edney, Matthew H. (2019) Cartography: The Ideal and Its History Chicago: The University of Chicago Press, 309 p. ISBN 978-0-226-60568-5